18F-Fluorodeoxyglucose Positron Emission Tomography and Computed Tomography With Magnetic Resonance for Diagnosing Adult-Onset Still's Disease - Bindoli, Sara; Galozzi, Paola; Magnani, Fabio; Rubin, Laura; Campi, Cristina; Doria, Andrea; Cecchin, Diego; Sfriso, Paolo (Frontiers in Medicine, 2020)
Objective. To assess the advantages of 18F-fluorodeoxyglucose (FDG) positron emission tomography and computed tomography with magnetic resonance (PET/CT-MR) in diagnosing and monitoring patients with adult-onset Still's disease (AOSD). Methods. Participants in this retrospective case-control study underwent whole-body 18F-FDG-PET/CT-MR imaging. All PET scans were qualitatively and semiquantitatively analyzed using standardized uptake values (SUVs) normalized to liver uptake, i.e. we calculated the ratio (SUVr) between the minimum, maximum and mean SUVs for different organs and tissues and the mean SUV for the liver. Disease activity scores were assessed using Pouchot’s criteria. Results. Eighteen patients diagnosed with AOSD and 24 controls (non-AOSD patients diagnosed with solid tumors, excluding lymphomas) were considered. A total of 38 PET/MR and 9 PET/CT scans were analyzed. AOSD patients had higher SUVr than controls. All SUVr differed significantly between the patient and control group for bone marrow, and for spleen the only difference lacking statistical significance concerned the ratio of the minimum SUV for spleen to the mean SUV for liver. Though limited in number, AOSD responders to therapy showed lower uptakes during the period monitored. No correlations were found between Pouchot’s scores and SUVr. Conclusion. Our data revealed higher spleen and bone marrow 18F-FDG uptakes on PET/CT and PET/MR images in AOSD patients than in controls. Together with clinical examinations and laboratory data, PET/CT and PET/MR seemed more reliable than Pouchot’s score in assessing disease activity.